Clays and Clay Minerals, Vol. 59, No. 2, 176–188, 2011. - Kim, Jinwook; Dong, Hailiang (My University, 2011)
Electron energy-loss spectroscopy (EELS), energy-filtered transmission electron microscopy (EFTEM), and high-resolution transmission electron microscopy (HRTEM) have been applied in mineralogy and materials research to determine the oxidation states of various metals at high spatial resolution. Such information is critical in understanding the kinetics and mechanisms of mineral-microbe interactions. To date, the aforementioned techniques have not been applied widely in the study of such interactions. In the present study, the three techniques above were employed to investigate mineral transformations associated with microbial Fe(III) reduction in magnetite. Shewanella putrefaciens strain CN32, a dissimilatory metal-reducing bacterium, was incubated with magnetite as the sole electron acceptor and lactate as the electron donor for 14 days under anoxic conditions in bicarbonate buffer. The extent of bioreduction was determined by wet chemistry and mineral solids were investigated by HRTEM, EFTEM, and EELS. Magnetite was partially reduced and biogenic siderite formed. The elemental maps of Fe, O, and C and red-green-blue (RGB) composite map for residual magnetite and newly formed siderite were contrasted by the EFTEM technique. The HRTEM revealed nm-sized magnetite crystals coating bacterial cells. The Fe oxidation state in residual magnetite and biogenic siderite was determined using the EELS technique (the integral ratio of L3 to L2). The integral ratio of L3 to L2 for magnetite (6.29) and siderite (2.71) corresponded to 71% of Fe(III) in magnetite, and 24% of Fe(III) in siderite, respectively. A chemical shift (~1.9 eV) in the Fe-L3 edge of magnetite and siderite indicated a difference in the oxidation state of Fe between these two minerals. Furthermore, the EELS images of magnetite (709 eV) and siderite (707 eV) were extracted from the electron energy-loss spectra collected, ranging from 675 to 755 eV, displaying different oxidation states of Fe in the magnetite and siderite phases. The results demonstrate that EELS is a powerful technique for studying the Fe oxidation-state change as a result of microbial interaction with Fe-containing minerals.
Application Of Electron Energy-loss Spectroscopy (eels) And energy-filtered Transmission Electron Microscopy (eftem) To The study Of Mineral Transformation Associated With Microbial fe-reduction Of Magnetite
gsccm59206-kim.pdf--1.74MB
Keywords: Periodicals; Geology; Electron Energy-loss Spectroscopy (EELS); Energy-filtered Transmission Electron Microscopy (EFTEM); Magnetite; Shewanella putrefaciens; Siderite